Comparative test of content uniformity of theophylline (150 mg/tab) tablets from two pharmaceutical houses in Costa Rica - Pérez-López, Esteban (2014)
Given the importance of the drug called theophylline, for use in patients with asthma, and given the high consumption of this drug in our country, we chose the product in tablets of 150 mg of theophylline from a pharmaceutical company that produces and distributes in the form generic that drug, along with manufactured by the Social Security Fund (CCSS) at the same dose of the same drug. We performed a comparative study of content uniformity test for theophylline tablets 150 mg, pharmaceutical house LISAN and the Social Security Fund. The content uniformity test was based on the absorption of the active ingredient and theophylline quantification at 272 nm for 10 samples of each house pharmaceutical, by using a UV/Vis, using distilled water as solvent. Proved that the method is selective, accurate and precise, and as a result was obtained that at all doses tested for each manufacturer, are in the range of 100% to 110%, with respect to labeling of the active ingredient in the tablets and with a relative deviation of no more than 2,5%, complying with the provisions of the Pharmacopoeia of the United States, to test for uniformity of content.